Fall calendar as a tracking and monitoring tool for older adults with a history of falls: a longitudinal study - Mariana Ignácio Sossai; Camila Bianca Falasco Pantoni; Livea Cristina da Silva; Mariana Luiz de Melo; Mel Silva de Sá; Karina Gramani-Say; Juliana Hotta Ansai (Geriatrics, Gerontology and Aging)
Objective: To verify adherence to and the applicability of a fall calendar as a tracking and monitoring tool among older people with a history of falls, and to identify which factors influenced their use of the calendar in their daily lives. Methods: This longitudinal study is derived from a randomized clinical trial conducted remotely in 2021 and 2022. Older people with a history of falls included in the MAGIC Program (Brazil) took part in the study. After an initial assessment that collected sociodemographic, health, and functional data, 16-week and 12-month follow-ups on falls were performed. Fall data were collected through monthly phone calls and the use of a fall calendar. Adherence to the fall calendar was investigated through descriptive analysis, fall rates were compared between calendar and monthly telephone data, the calendar was analyzed for sensitivity and specificity, and possible influences on adherence to the fall calendar were identified through regression analysis. Results: In this sample of 56 older adults, adherence to the calendar was unsatisfactory. The fall calendar presented 21.2% sensitivity and 18.7% specificity compared to monthly phone calls. Moreover, sociodemographic, health, and functional factors did not influence adherence to the calendar. Conclusion: There was low adherence to the fall calendar, and clinical and sociodemographic factors did not influence adherence. Further randomized clinical trials that screen falls through monthly phone calls are recommended in Brazil.